Recombinant expression of native Tritrypticin and optimisation of an In vivo biosynthesis platform for high-throughput peptide therapeutics discovery - Mahendran, Arun Suria Karnan (2025)
The global increase in antibiotic-resistant bacteria poses a public health threat, heightened by overuse of antibiotics in livestock farming, the food industry, and healthcare. This demands for novel antimicrobial compounds to address the diminishing inefficacy of current antibiotics. Antimicrobial peptides (AMPs) ubiquitous in organisms' innate immune systems show potential with their broad-spectrum activity. This study investigates on Tritrypticin (TTC), a 13-residue bactericidal peptide rich in tryptophan. Derived from the C-terminal domain of the porcine bone marrow precursor molecule C12, that demonstrates antimicrobial properties against pathogens like Escherichia coli and Salmonella typhimurium. This study addresses the challenges in producing AMPs using recombinant expression in E. coli BL21 (DE3) and utilisation of the inducible, self-cleavable fusion protein, Synechocystis sp. (Ssp) DnaB intein, demonstrating potential for higher yields and scalable recombinant expression of AMP. The study identified the optimal recombinant protein expression conditions at low induction parameters (0.1 mM IPTG, 15°C, 200 rpm agitation, and 18 hours). Induction of the Ssp DnaB intein cleavage to release TTC was observed at pH 5, incubated at 25°C for 8 hours, and further enhanced with supplementation of non-ionic detergent and solvents such as Tween-20, Triton X-100, and dimethyl sulfoxide (DMSO). The extracellular secretion of the TTC peptides mediated by incorporating signal peptides (SPs), Outer Membrane Protein A (OmpA) and novel signal peptide 4 (NSP4), enabled the identification of antibacterial activity of TTC towards Bacillus subtilis ATCC 6633 through bacterial agar screening, demonstrating the excretion of TTC from E. coli BL21 (DE3) host. Utilising directed evolution techniques, error-prone PCR (epPCR) with imbalanced nucleotides and MnCl2 supplement, accelerated the generation of a diverse pool of mutant TTC producers, identification up to 66% of candidates and identified peptide mutations with arginine that enhanced antibacterial activity with larger inhibition zones against B. subtilis through the high-throughput bacterial screening method. Overall, the study investigates the potential of expressing AMPs in recombinant expression systems to allow more efficient peptide production and generate mutant peptides with potentially enhanced antimicrobial activity, rapidly identified by the high-throughput screening method. This research contributes to ongoing efforts to identify novel antibiotics to combat antibiotic-resistant pathogens and address the growing threat of antimicrobial resistance.